2020
DOI: 10.1101/2020.03.09.20033118
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiological, Clinical Characteristics and Outcome of Medical Staff Infected with COVID-19 in Wuhan, China: A Retrospective Case Series Analysis

Abstract: Backgrounds Since December 2019, a novel coronavirus epidemic has emerged in Wuhan city, China and then rapidly spread to other areas. As of 20 Feb 2020, a total of 2,055 medical staff confirmed with coronavirus disease 2019 (COVID-19) caused by SARS-Cov-2 in China had been reported. We sought to explore the epidemiological, clinical characteristics and prognosis of novel coronavirus-infected medical staff. MethodsIn this retrospective study, 64 confirmed cases of novel coronavirus-infected medical staff admit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 30 publications
2
59
1
Order By: Relevance
“…We initially identified 73 articles based on our search strategy, 64 of which were excluded after title, abstract, or full-text reading, because they were review articles, did not report IL-6 levels, or did not classify the condition of COVID-19 patients as non-severe and severe. Finally, only nine studies were included in this meta-analysis [1][2][3][4][5][6][7][8][9]. Although the heterogeneity was considerably high (I 2 = 89%; P < 0.00001), we observed that IL-6 levels were significantly increased in COVID-19-infected patients with severe condition compared with those with non-severe condition (SMD = 0.71, 95%CI −0.31-1.12, P = 0.0005) ( Fig.…”
Section: Disponible En Ligne Surmentioning
confidence: 99%
“…We initially identified 73 articles based on our search strategy, 64 of which were excluded after title, abstract, or full-text reading, because they were review articles, did not report IL-6 levels, or did not classify the condition of COVID-19 patients as non-severe and severe. Finally, only nine studies were included in this meta-analysis [1][2][3][4][5][6][7][8][9]. Although the heterogeneity was considerably high (I 2 = 89%; P < 0.00001), we observed that IL-6 levels were significantly increased in COVID-19-infected patients with severe condition compared with those with non-severe condition (SMD = 0.71, 95%CI −0.31-1.12, P = 0.0005) ( Fig.…”
Section: Disponible En Ligne Surmentioning
confidence: 99%
“…On the frontlines of defense against the virus, HCW may experience increased risk of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection due to close contact with highly infectious patients 1 and, commonly, insufficient access to personal protective equipment (PPE) 2 . The plight of HCW during the pandemic has been widely noted [3][4][5][6][7][8] ; as of April 9, 2020, 9,282 known COVID-19 cases among U.S. HCW had been reported to the Centers for Disease Control and Prevention (CDC) 9 . Of HCW with COVID-19, 55% reported that their only known exposure was the in the health care setting.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently [39], no firm conclusions could be drawn from studies evaluating the rates of current smokers in Covid-19. All these studies [40][41][42][43][44][45][46][47][48], although reporting low rates of current smokers, ranging from 1.4 % to 12.5 %, did not take into account the main potential confounders of smoking including age and sex. In the study that two of us are reporting [1], the rates of current smoking remain below 5 % even when main confounders for tobacco consumption, i.e.…”
mentioning
confidence: 99%